THE IDENTIFICATION OF STROKE RISK FACTOR AT RSUD BIMA IN 2015 - A. Haris A. Haris; Martiningsih Martiningsih (poltekkes kemenkes mataram, 2016)
Abstract: Stroke is a clinical syndrome with sudden onset of focal neurologic dysfunction, which lasts for 24 hours or more, or it can cause death without any other apparent cause other than vascular. The prevalence of stroke in Indonesia based on the diagnosed of health personnel by 7 per mile ( West Nusa Tenggara 4.5) and diagnosed by health worked or symptoms of 12,1 (NTB 9,6 ) per mile. Stroke occurs as a result of the inability of patients or individuals who have the risk factors avoid or control risk factors. The purpose of research to identify and explain the risk factors associated with the occurrence of stroke. This research method is descriptive analytic research with cross-sectional design, in stroke patients were treated in Bima District Hospital in the period July-October 2015 that met the inclusion criteria with a total sample of 85 respondents. The results of research based on the risk factors that can’t be changed to show the majority of the respondent's age is the category of the elderly (> 55 years) is 62 persons (72.9%) and male gender are 57 people (67.1%) and factor the risk from family history / descendants as many as 65 respondents (76.5%). while based on modifiable risk factor analysis results showed that the risk factors of hypertension are 77 respondents (90.6%), diabetes risk factors as much as 52 respondents (61.2%), other risk factors related to smoking is that most 58 respondents were smokers or had smoked a minimum. recommendation of this research is necessary to further research with a larger sample size and develop the variables that will be researched associated with behaviors that contribute to stroke.